Pendelaar tussen afstand en nabijheid : getuigenissen van buddy's over mensen met aids - D'Hulster, Ronny; Bolle, Greta; Jacobs, Lieven; Vercauteren, Robert; Versées, Mieke (Kapellen : Uitgeverij Pelckmans, 1999)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie